Micropropagation of Lilium candidum L. : a rare and native bulbous flower of Turkey - Burun, Betül; Sahin, Oral (Bangladesh Journal of Botany, 2013)
Lilium candidum bulb scales were cultured on MS containing different doses and combinations of NAA, BA, Kn and 2iP. Maximum bulblet formation was 88.2% in MS supplemented with 0.1 mg/l NAA + 0.01 mg/l BA and the average number of bulblets per explant was 2.9. DOI: http://dx.doi.org/10.3329/bjb.v42i1.15913 Bangladesh J. Bot. 42(1): 185-187, 2013 (June)